2020
DOI: 10.3390/bioengineering7020054
|View full text |Cite
|
Sign up to set email alerts
|

Andean Sacha Inchi (Plukenetia Volubilis L.) Leaf-Mediated Synthesis of Cu2O Nanoparticles: A Low-Cost Approach

Abstract: In this work, Andean sacha inchi (Plukenetia volubilis L.) leaves were used to prepare monodispersed cuprous oxide (Cu2O) nanoparticles under heating. Visual color changes and UV-visible spectroscopy of colloidal nanoparticles showed λmax at 255 nm, revealing the formation of copper oxide nanoparticles. Transmission electron microscopy and dynamic light scattering analysis indicated that the prepared nanoparticles were spherical with an average size of 6–10 nm. The semi-crystalline nature and Cu2O phase of as-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
(67 reference statements)
1
12
0
2
Order By: Relevance
“…Energy dispersive x-ray (Edx) spectroscopy gives elemental analysis, TEM, and selected area electron diffraction (SAEd) to show the structure pattern of the material. As reported by (Kumar et al, 2017) the AgNP's uV-Vis spectra occur at λmax = 435 nm, TEM indicates the crystalline structure and spherical shaped particles in a size range of 12 to 50 nm. on the other hand, (Nayak et al, 2016) have reported that the synthesized silver nanoparticles could be preliminarily identified by color, which gives the formation of silver nanoparticles and is further validated by using uV-Visible spectroscopy.…”
Section: Characterization Techniquessupporting
confidence: 64%
See 2 more Smart Citations
“…Energy dispersive x-ray (Edx) spectroscopy gives elemental analysis, TEM, and selected area electron diffraction (SAEd) to show the structure pattern of the material. As reported by (Kumar et al, 2017) the AgNP's uV-Vis spectra occur at λmax = 435 nm, TEM indicates the crystalline structure and spherical shaped particles in a size range of 12 to 50 nm. on the other hand, (Nayak et al, 2016) have reported that the synthesized silver nanoparticles could be preliminarily identified by color, which gives the formation of silver nanoparticles and is further validated by using uV-Visible spectroscopy.…”
Section: Characterization Techniquessupporting
confidence: 64%
“…hence, silver nanoparticles can help to improve the performance of antibiotics. (Kumar et al, 2017) were concluded that obtained silver nanoparticles show good antioxidant efficiency (>78%, 0.1 mM) against 1,1-diphenyl-2-picrylhydrazyl. The synthesis process is an environmental ecofriendly and promising aspirant for biomedical applications.These particles exhibit antibacterial activity against bacteria.…”
Section: Bacterial Action Of Biosynthesized Silver Nanoparticlesmentioning
confidence: 95%
See 1 more Smart Citation
“…The UV-Vis absorption spectra revealed an absorbance as portrayed in Fig. 1a (black line) from ~ 300 to ~ 350 nm suggesting formation of copper oxide nanoparticles 40,41 . Albeit copper nanoparticles exhibit intense localized surface plasmon resonance in the visible region, the nanoparticles in the current study didn't show any peak in the visible region, while distinct broad band was observed at ~ 320 for surfactant stabilized copper oxide nanoparticles.…”
Section: Results and Discussion Characterization Of Copper Oxide Nanomentioning
confidence: 98%
“…Albeit copper nanoparticles exhibit intense localized surface plasmon resonance in the visible region, the nanoparticles in the current study didn't show any peak in the visible region, while distinct broad band was observed at ~ 320 for surfactant stabilized copper oxide nanoparticles. This could be attributed to the formation of cuprous oxide nanoparticles (Cu 2 O) 40,42,43 .…”
Section: Results and Discussion Characterization Of Copper Oxide Nanomentioning
confidence: 99%